The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1161/01.str.30.9.1907
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dihydropyridine Calcium Channel Blockers Inhibit Plasma and LDL Oxidation and Formation of Oxidation-Specific Epitopes in the Arterial Wall and Prolong Survival in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Background and Purpose-Calcium-channel blockers (CCBs) reduce systolic blood pressure and stroke-related mortality in stroke-prone spontaneously hypertensive rats (SPSHR). Brain ischemia is associated with loss of intracellular antioxidants. Increased formation of oxygen radicals and oxidation of LDL may enhance arterial vasoconstriction by various mechanisms. CCBs that also exert antioxidative properties in vitro may therefore be particularly useful. To investigate such antioxidant effects in vivo, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…It was previously reported that calcium channel blockers could inhibit the oxidation of LDL. [44][45][46] Benidipine also has the same action, because the concentration of anti-oxLDL antibody decreased significantly after benidipine treatment in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…It was previously reported that calcium channel blockers could inhibit the oxidation of LDL. [44][45][46] Benidipine also has the same action, because the concentration of anti-oxLDL antibody decreased significantly after benidipine treatment in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…Recent data in strokeprone hypertensive rats have demonstrated that exogenous administration of the antioxidant, vitamin E, or calcium antagonists with antioxidant properties reduces their long-term mortality. 13 On the other hand, studies in humans have yielded conflicting effects of vitamin E treatment on clinical end points (see review 28 ). However, atherogenesis is a complex disease, 29 and it is possible that the lower susceptibility of intracranial arteries to cholesterol-induced atherogenesis results mainly from the coincidence of lower blood pressure 1 and decreased susceptibility to endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Statins reduce the incidence of nonfatal stroke in coronary heart disease patients [1][2][3] but are apparently less effective in reducing the mortality from ischemic stroke. [1][2][3] Although intracranial arteries eventually develop atherosclerotic lesions, the onset of atherogenesis occurs much later in life, and the severity of the lesions at various ages is consistently less than that in extracranial arteries in humans, 2,4 -9 nonhuman primates, 10 rhesus and cynomolgus monkeys, 11 spontaneously hypertensive rats, 12,13 cholesterolSee Editorial Comment, page 2479 fed rabbits, 11 and Watanabe heritable hyperlipidemic rabbits. 14 To date, it is unknown whether the difference in atherosclerosis is due to anatomic differences between intracranial and extracranial arteries, systemic differences (eg, lower local blood pressure), or other differences in atherogenic mechanisms.…”
mentioning
confidence: 99%
“…The gastric damage score was calculated for each stomach by summing the lengths of all erosions (23,24,32,33). Carotid arteries were perfused with phosphate-buffered paraformaldehyde (4%, 0.1 mol͞liter, pH 7.3) for histology or normal saline for immunohistochemistry assessed by computer-assisted imaging analysis (34)(35)(36). Carotid arteries were serially sectioned into 15-20 slices (10 M) with a rotating diamond-coated knife, and sections were stained with toluidine blue.…”
Section: Methodsmentioning
confidence: 99%